Exploring men's involvement in family planning in Lao PDR. Issue 8 (17th November 2021) - Lorkuangming, Vanly; Beban, Alice; Stewart-Withers, Rochelle
ABSTRACT: This study explores men's involvement in family planning programmes in a rural area of Lao PDR. Data from interviews with ethnic minority Mangkong couples and women suggest that while there are some positive outcomes from men's involvement in family planning, such as increased spousal communication and shared responsibility for housework and childcaring, the current family planning model still places the burden on women as the main contraceptive users. This results in the exclusion of men from obtaining family planning information and services. Recommendations are provided for creating family planning programmes that are context-specific and gender-equitable.